2023
DOI: 10.1039/d2cc05152d
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light driven reaction of CO2 with alcohols using a Ag/CeO2 nanocomposite: first photochemical synthesis of linear carbonates under mild conditions

Abstract: The first photochemical synthesis of linear carbonates from the reaction of CO2 with alcohols using silver-doped ceria nanocomposite at room temperature under visible light irradiation is described. DFT calculations suggested...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In addition, the proposed mechanism was supported by a few mechanistic experiments conducted mostly using 1 H NMR. Very recently, Jain et al reported the first photochemical synthesis of linear carbonates from the reaction of CO 2 with alcohols using a silver-doped ceria nanocomposite at room temperature under visible light irradiation [48]. In this context, we decided to investigate the synthesis of cyclic carbonates through a onepot multicomponent metal-free process which merges the photo-promoted Atom Transfer Radical Addition (ATRA) of a perfluoroalkyl iodide (Rf-I) onto unsaturated alcohols with the Lewis-base-promoted carboxylative cyclization (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the proposed mechanism was supported by a few mechanistic experiments conducted mostly using 1 H NMR. Very recently, Jain et al reported the first photochemical synthesis of linear carbonates from the reaction of CO 2 with alcohols using a silver-doped ceria nanocomposite at room temperature under visible light irradiation [48]. In this context, we decided to investigate the synthesis of cyclic carbonates through a onepot multicomponent metal-free process which merges the photo-promoted Atom Transfer Radical Addition (ATRA) of a perfluoroalkyl iodide (Rf-I) onto unsaturated alcohols with the Lewis-base-promoted carboxylative cyclization (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%